Insecticide resistance and mechanisms of aedes aegypti (Diptera: Culicidae) in Yogyakarta, Indonesia - Budi Mulyaningsih; Sitti Rahmah Umniyati; Tri Baskoro Tunggul Satoto; Ajib Diptyanusa; Dwi Aris Agung Nugrahaningsih; Yahiddin Selian (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
For several decades, applications of organophosphates and pyrethroids insecticides have been extensively used to control Aedes aegypti as the primary dengue vector. Hence it is important to study dengue vector resistance status and its mechanisms in relation to long term use of insecticides. This study aimed to determine the resistance status and to characterize mechanisms of Ae. aegypti to organophosphates and pyrethroids using biological, biochemical and molecular assays. Larvae and puppae of Ae. aegypti were collected in the field of Plosokuning, Minomartani, Sleman, Yogyakarta, Indonesia. The biological assay was carried out using CDC Bottle Bioassay to test the resistant status to malation and cypermetrin. The biochemical assay was conducted using microplate assay with substrate α-naphthyl acetate to test the presence of esterase elevated activity, and the molecular assay was done using PCR with AaSCF7 and AaSCR7 primer to detect of point mutation at 1534 site, that located in the area of segment 6 of domain III. The biological assay showed Ae. aegypti suggests the possibility of resistance to malathion (mortality 82%) that needs to be confirmed further and already resistant to cypermetrin (mortality 76%). The biochemical assay of Ae. aegypti showed the presence of non-specific esterase elevated activity. The PCR method showed specific DNA bands were formed with the size of 748bp, and with sequencing showed there has been F1354C point mutation of voltage gated sodium chanel gene in the area of segment 6 of domain III. Long term use of insecticides did not successfully eliminate the targeted dengue vector, because Ae. aegypti mosquitoes were resistant to both insecticides. The results demonstrate the importance of designing better health policies regarding insecticide usage